Effect of Community Participation in Education on Quality of Education: Evidence from a Developing Context - Ahmad, Iqbal (Journal of Education and Vocational Research, 2013)
Education is an activity in collaboration. Without community participation, education cannot achieve its goals and without education society cannot think of development. A plethora of research exists on community participation in education and its outcomes. However, meager studies have been carried out to examine the relationship between community participation and quality of education. Although quality of education cannot be determined by one or two indicators. Research has already discovered many indicators of quality of education. But this study specifically investigated into three essential indicators which are contextually relevant to a developing country. The three main indicators investigated in relation with community participation were access, retention and attendance. The main aim of this study was to find out whether or not community participation in education reduces the issues of access, retention and attendance at secondary school level. To collect data, the study surveyed 200 (female) and 300 (males) total N=500 government secondary schools teachers in Khyber Pakhtunkhwa province of Pakistan. Data were collected, collated and statistically computed using Pearson Correlation and ANOVA to determine a correlation between the independent variable (community participation in education) and the three indicators of quality of education such as access, retention and attendance as dependent variables. Results of the study indicated a significantly positive correlation between community participation and all the three indicators of quality of education. The study proposes community participation in education as the high positive predictor of access to education, retention and attendance.